WEED FLORA OF DIFFERENT FARM BLOCKS IN BLOCK-1 OF MUDA RICE GRANARY IN PENINSULAR MALAYSIA - Mahfuza Begum,; Abdul Shukor Juraim,; Azmi Man,; Syed Omar Syed Rastan,; Rajan Amartalingam, (Tropical Life Sciences Research, 2008)
A survey on the major weed flora of rice fields in Block-1 of Muda rice granary area, Peninsular Malaysia, indicated there were 28 weed species belonging to 15 families in this area. Of these, 13 species were broad-leaves, six grasses, six sedges, and three aquatics. Sorenson’s Index of Similarity (S) indicated that at least 24.2% of the listed species occurred in five blocks. Oryza sativa complex (padi angin) and Echinochloa crus-galli appeared wide spread species in all blocks, but were most abundant in block AI, BI and DI having a greater proportion of severe infestations (scores of 3 to 5: 31%–50% weed cover). Leptochloa chinensis was the most frequent and abundant species in block AI and EI having the severity score of 3, i.e. 30% and 20% (score of 2) weed coverage in block BI and CI, respectively. Other weed species such as Ischaemum rugosum, Fimbristylis miliacea, Scirpus grossus, Sphenoclea zeylanica and Cyperus difformis were having 20% (score of 2) weed coverage. The hierarchy of weed type based on the percentage of field infested ratio was in the order of: grasses (G) > broad-leaved weeds (BL) > sedges (SG) > aquatics (AQ) in all blocks with a slight difference in block AI, where sedges were dominant instead of broad-leaved weeds, aquatic weeds were totally absent and grasses were predominant as compared to other blocks. Satu peninjauan terhadap flora rumpai di Blok-1, kawasan padi Muda, Semenanjung Malaysia, menunjukkan terdapat 28 spesies rumpai tergolong dalam 15 famili di kawasan ini. Tiga belas spesies adalah rumpai daun lebar, enam daun tirus, enam rusiga, dan tiga akuatik. Indeks Kesamaan Sorenson (S) menunjukkan sekurang-kurangnya 24.2% spesies berlaku di kesemua lima blok. Oryza sativa kompleks (padi angin) dan Echinochloa crus-galli didapati dominan di semua blok, tetapi paling banyak di blok AI, BI dan DI dengan mempunyai nisbah serangan yang serius (skor 3 ke 5: 31%–50% litupan rumpai). Leptochloa chinensis adalah yang paling dominan di blok AI dan EI dengan mempunyai skor keterukan 3, iaitu masing-masing 30% dan 20% litupan rumpai di blok BI dan CI. Spesies-spesis lain seperti Ischaemum rugosum, Fimbristylis miliacea, Scirpus grossus, Sphenoclea zeylanica dan Cyperus difformis mempunyai tahap skor sehingga 20% (skor 2) litupan rumpai. Hierarki jenis rumpai mengikut nisbah peratus serangan keseluruhan blok adalah: daun tirus (G) > daun lebar (BL) > rusiga (SG) > akuatik (AQ) dengan sedikit berbeza pada blok AI, di mana rusiga adalah lebih dominan daripada rumpai daun lebar, rumpai akuatik tidak didapati dan rumpai daun tirus adalah pradominan berbanding dengan blok lain.